Numerical investigations of gas–liquid two-phase flows in microchannels. (February 2018) - Lou, Qin; Yang, Mo; Xu, Hongtao
Immiscible gas–liquid two-phase flows with an initial stochastically distribution, which are driven by a constant body force in a period microchannel of5 - 20 μ m in width, are studied using the lattice Boltzmann method under various conditions. Continuous dynamic behaviors of bubbles and droplets including breaking up, coalescence, deformation, and mass exchange between them are observed. The flows reach to their steady state when the rate of breaking up and coalescence are in balance, and no mass exchange occurs. The simulation results show that the steady-state flow regimes depend strongly on the viscous force, surface tension, inertial force, channel width, and wettability of the solid surface. Specially, it is found that slug flow is more probable to occur for the small channel width at the same volume fraction. And the shape of bubble in the slug flow is determined by the wettability of the solid wall. Furthermore, the shape and number of bubbles at steady state are related to surface tension, viscous force, and inertial force. It is also found that the initial bubble distributions have slight effects on the flow regimes at steady state.